2001
DOI: 10.1016/s0735-1097(00)01046-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of myocardial perfusion during graded coronary stenosis by real-time myocardial contrast echo refilling curves

Abstract: In an open-chest dog model, parameters derived from microbubble refilling of the imaging field by real-time MCE correlate well with myocardial blood flow and can identify coronary stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 7 publications
3
61
0
1
Order By: Relevance
“…In cardiac imaging, CEUS has an established role in left ventricle opacification and endocardial border definition to assess myocardial function and ejection fraction [55][56][57]. The quantification of myocardial perfusion through reperfusion kinetics [57,58] is accurate in the detection of coronary artery stenosis [59], and provides similar results to SPECT and stress echocardiography [60]. In normal conditions during pharmacological stress, the myocardium is fully replenished by microbubbles 1 to 1.5 s after the end of a high-transmit-power pulse train [58], while in regions subserved by stenotic coronary arteries the rate of filling is slower depending upon the severity of stenosis (Fig.…”
Section: Clinical Applications Of Organ Perfusionmentioning
confidence: 99%
“…In cardiac imaging, CEUS has an established role in left ventricle opacification and endocardial border definition to assess myocardial function and ejection fraction [55][56][57]. The quantification of myocardial perfusion through reperfusion kinetics [57,58] is accurate in the detection of coronary artery stenosis [59], and provides similar results to SPECT and stress echocardiography [60]. In normal conditions during pharmacological stress, the myocardium is fully replenished by microbubbles 1 to 1.5 s after the end of a high-transmit-power pulse train [58], while in regions subserved by stenotic coronary arteries the rate of filling is slower depending upon the severity of stenosis (Fig.…”
Section: Clinical Applications Of Organ Perfusionmentioning
confidence: 99%
“…Neither closed-chest MCE nor end-systolic triggering acquisition was validated with the established technique of microspheres; however, real-time acquisition is an accepted technique for MBF estimation. 44,45 Finally, we did not quantify absolute MBF. Recently, Vogel et al 14 demonstrated that normalizing A␤ obtained in the myocardial walls by the LV cavity signal intensity provides absolute measurements of MBF in humans.…”
Section: Raher Et Al Murine Contrast Echocardiographymentioning
confidence: 99%
“…However, previous techniques using intermittent harmonic imaging have demonstrated limitations regarding the wall motion analysis and time required for image acquisition (2,5,7). Real time myocardial contrast echocardiography (RTMCE) is a recent technique that uses very low mechanical energy allowing the evaluation of microbubbles in the coronary circulation without their destruction, and simultaneous assessment of myocardial perfusion and function (7)(8)(9)(10).…”
Section: Pmm Dourado Et Almentioning
confidence: 99%